Case report: Novel compound-heterozygous mutations in the TCN2 gene identified in a chinese girl with transcobalamin deficiency - Luo, Juan; Guo, Hongxi; Feng, Lifang; Yang, Luhong; Chen, Xiaoqian; Du, Tingting; Hu, Man; Yao, Hui; Chen, Xiaohong (Frontiers in Genetics, 2022)
Transcobalamin II (TC II) deficiency is a rare autosomal recessive disease characterized by megaloblastic anemia. It is caused by cellular vitamin B12 depletion, which subsequently results in elevated levels of homocysteine and methylmalonic acid. TC II deficiency is usually diagnosed by genetic analysis of the TCN2 gene. Here, we described a 2.2-month-old Chinese girl with TC II deficiency presenting with diarrhea, fever and poor feeding. Whole-exome sequencing detected a pair of compound-heterozygous mutations in TCN2 gene, c.1031_1032delGA (p.R344Tfs*20) and c.754-12C>G. To our knowledge, it is the first time that they were identified and reported in TC II deficiency. This study contributes to a better understanding of the TC II deficiency, expanding the spectrum of TCN2 mutations in this disorder and also supporting the early diagnosis and proper treatment of similar cases in the future.